Pour une géographie de la démocratie - Michel Bussi (L'Espace Politique)
The field of the geography of power is no more reduced to the study of conflicts because power relationships take more various forms, that is to say negotiations, cooperation and so on. The control upon space no more exclusively belongs to those who are able to conquer new territories or to defend themselves. It belongs more and more to those who are able to associate, in order to reach common goals, to build up efficient networks, to establish contractual relations and eventually to adapt political territories without shifting their limits. Democracy, broadly speaking, may appear as a new paradigm of major importance in the field of geographical studies. It brings into question the classical approaches and the traditional bases of political geography and spatial development and planning. Nevertheless, democracy is never presented and put ahead as a major concept by the geographers. This paper fully addresses this problem. First, it aims at explaining such a situation by setting out various assumptions: - the gap between geography and democracy is a consequence of the gap lying between geographers and politics ; - the gap between geography and democracy is due to the fact that the study of power relations in geography is too much oriented to purely geopolitical issues ; - Democracy is standing at the crossroads of politics and sociology ;- The gap between geography and democracy is due to the fact that democracy has only recently emerged as a widespread, if not universal, model of social relations ; - The gap between geography and democracy is a consequence of the primacy of a bottom-up method in political and social relations, which means that individual freedom is more important that anything else, while geography is more based on a top-down approach ;- Democracy and geography are the same thing. Secondly, it tries to set forth the various research fields where geography, as an academic discipline, and democracy may show common subjects of concern. To encourage the development of the geography of democracy is a way to open new fields of research to geographers: comparisons of various types of representative democracies, study of various types of local participations in local development policies, study of cooperative or non-cooperative interactions in the field of local development, etc. Nevertheless, even if geography can be finally considered as a mean towards peace, it must not be necessarily conceived as an exclusively angelic discipline. It also must be able to propose a global and comprehensive method to study various types of cooperation between various actors, because the territorial (spatial) mediation still remains a sine qua non condition to any kind of social contract.